2019
DOI: 10.3390/ijms20092366
|View full text |Cite
|
Sign up to set email alerts
|

Glycation of Plant Proteins: Regulatory Roles and Interplay with Sugar Signalling?

Abstract: Glycation can be defined as an array of non-enzymatic post-translational modifications of proteins formed by their interaction with reducing carbohydrates and carbonyl products of their degradation. Initial steps of this process rely on reducing sugars and result in the formation of early glycation products—Amadori and Heyns compounds via Schiff base intermediates, whereas their oxidative degradation or reactions of proteins with α-dicarbonyl compounds yield a heterogeneous group of advanced glycation end prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 191 publications
(231 reference statements)
2
30
0
Order By: Relevance
“…In fact, it has been reported that MG forms adducts with arginine, lysine and cysteine residues of proteins, generating advanced glycation end-products (AGEs) [10,23]. AGEs adversely affect the whole organism, causing oxidative damage to key cellular components [49,50,51]. In order to assess the accumulation of MG-protein adducts in glyI4 mutant, Western blot analyses with antibody detecting MG-adducts were carried out (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been reported that MG forms adducts with arginine, lysine and cysteine residues of proteins, generating advanced glycation end-products (AGEs) [10,23]. AGEs adversely affect the whole organism, causing oxidative damage to key cellular components [49,50,51]. In order to assess the accumulation of MG-protein adducts in glyI4 mutant, Western blot analyses with antibody detecting MG-adducts were carried out (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, in our work, taurine reduced under drought. About the specific responses of each variety to drought, the sugars threose and rhamnose were not found at 12DI, both accumulated at PI and reduced the abundance at 4DI, in the CTC15 variety.Threose is one of the products from the oxidative degradation ascorbate, an important oxidant (Shumilina et al, 2019). Contrary to our findings, this sugar was reported to accumulate in roots of alfafa plants submitted to alkali stress (Song et al, 2017) and accumulate under drought in leaves, stem, root, and root colar in Caragana korshinskii , which is described as a highly drought tolerant plant (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, these include hemoglobin, transcription factors and mitochondrial proteins, which may be associated with mitochondrial dysfunction in disease, aging, stress and apoptosis (Rabbani & Thornalley, 2012). In plants, studies of glycation hotspots in Arabidopsis, B. napus and recently in legume nodules indicate heavy glycation of plant proteomes in comparison to animals (Shumilina et al, 2019) and that stress conditions such as drought, heat and light primarily target glycations to the chloroplast, the site of production of higher levels of sugars (Chaplin et al, 2019).…”
Section: Different Shades Of Methylglyoxal: Cytotoxin or A Signal mentioning
confidence: 99%